Cross-country efficiency of secondary education provision: a semi-parametric analysis with non-discretionary inputs - Afonso, António (2006)
We address the efficiency of expenditure in education provision by comparing the output (PISA results) from the educational system of 25, mostly OECD, countries with resources employed (teachers per student, time spent at school). We estimate a semi-parametric model of the education production process using a two-stage procedure. By regressing data envelopment analysis output scores on non-discretionary variables, both using Tobit and a single and double bootstrap procedure, we show that inefficiency is strongly related to GDP per head and adult educational attainment.